Basic assessment and prioritization of quality indicators of medical education in Iran's higher education system - Shafiezad Abkenar , Batool; Mousavi, Seyed Nematullah; Kamali , Mahdi; Mohebbi , Mohammad (Social Determinants of Health, 2024)
Background: Higher education is the fundamental cornerstone for the development of society. The objective of this research was to conduct an initial assessment and ranking of quality indicators for medical education inside Iran's higher education system. Methods: The ARDL method was used. The expected relationship between the research variables was investigated, and then, the long-term and short-term coefficients were estimated in the second stage. To test the existence of long-term relationship, Banerjee, Dolado and Master's method was used. This test was performed based on the t-statistics. Long-term coefficients were extracted from ARDL model and dynamic error correction model. The investigation of the measures of educational quality in Iran's higher education system relied on the Gulpak article model and data obtained from the Statistics Center and the Central Bank of Iran. Results: Family cultural characteristics, parental education, parental economic status, location of residence, gender, and marital status were all independent variables that influenced the need for higher education. Additionally, there is a notable correlation between the number of children and the educational attainment of those children. Family background variables and cultural factors exhibit strong interdependence and directly influence an individual's perception of ongoing schooling. The variables of economic growth, consumer price index, and government spending in the education sector have a positive and statistically significant impact on the demand for higher education in Iran. Conclusion: By identifying the primary markers of educational quality, one may pinpoint the barriers to academic advancement and therefore enhance the overall quality of education.